Aproximación al uso de la segunda pantalla en la estrategia publicitaria de marcas de éxito en España - Dr. José BERENGUEL FERNÁNDEZ, (Fonseca, Journal of Communication, 2023)
The second screens campaigns combine the already known potential of television with the generation of reviews through social networks, primarily Twitter, and generate a social audience that is of special interest to advertisers. This research has as general objective to approach the use of the second screen as an effec-tive advertising tool in the campaigns of successful brands in Spain